Staged urethroplasty: comparison of early functional results and quality of life in mesh graft and buccal mucosa technique - Pfalzgraf, Daniel Philipp (The Canadian journal of urology, 2015)
Introduction: To assess bothersome results of surgery and changes in quality of life (QoL) in patients with two-staged urethral reconstruction. In patients requiring two-staged urethroplasty a functional corpus spongiosum is usually absent, and complications such as urinary dribbling, ejaculation problems and penile deviation can be expected. Data on these complications, patient satisfaction and QoL is limited. Materials and methods: Retrospective analysis by chart review and a standardized questionnaire of 19 consecutive patients with urethral strictures treated by two-staged urethroplasty with buccal-mucosa-graft or mesh-graft. Results: Overall success rate was 84%. Mean follow up 11.2 months, mean length of graft 10 cm (3 cm-18 cm). Urinary stress incontinence occurred in 3 patients (16%). No penile shortening occurred in 9 (47%), no deviation in 11 (58%). Two patients (11%) reported a disturbing alteration in glans sensitivity. Regarding bother by both surgeries and the interval in between, 21% judged the first surgery as hardly or not bothersome. The time in between surgeries was hardly or not bothersome in 52% and the second surgery not or hardly bothersome in 26%. Overall satisfaction with surgery was high (79%) and an improvement in QoL was reported by 63%. Differences between the two groups did not reach statistical significance. Conclusion: Two-staged urethroplasty is a viable therapeutic option in patients with severe spongiofibrosis. However, specific counseling for possible complications is of utmost importance.
Gesehen am 01.02.2018